Bolt’s Farm Cave System dans le Cradle of Humankind (Afrique du Sud) : un exemple d’approche multidisciplinaire dans l’étude des sites à primates fossiles - Dominique Gommery; Frank Sénégas; Lazarus Kgasi; Nonhlanhla Vilakazi; Brian Kuhn; James Brink; Martin Pickford; Andy IR Herries; John Hancox; Thibaud Saos; Loïc Ségalen; Julie Aufort; et al. (Revue de Primatologie)
The Cradle of Humankind in South Africa, recognized as World Heritage by UNESCO since 1999, contains fossil sites which have yielded hominid remains and/or non-human primates (Cercopithecoidea). Robert Broom was the first to prospect for fossils at Bolt's Farm Cave System (or BFCS), and this since 1936. Research only became regular in 2006 with the creation of the HRU (Hope (Human Origins and Past Environment) Research Unit). BFCS is best known for yielding remains of large cats. Yet some fossils of Cercopithecoidea discovered at BFCS are considered to be references in palaeoprimatology: BF42 (Cercopithecoides williamsi) and BF43 (Parapapio broomi). Waypoint 160 at BFCS yielded the oldest remains of nonhuman primates in the Cradle of Humankind which are dated to the Pliocene. For more information about the geological and palaeoenvironmental context, excavations were conducted since 2011 in some loci based on the surveys carried out by members of HRU. The present challenge is to obtain the maximum amount of data concerning palaeobiodiversity, including the microfauna which must be extracted from the breccia by acid preparation techniques, study of the conditions of fossilization and the preservation of fossils, as well as the determination of the ages of the fossils.